Comparison of tensiomyographic contractile properties of the knee muscles between endurance and power athletes - Ipavec, M.; Kukec, Ž.; Kacin, A. (Isokinetics and Exercise Science, 2023)
BACKGROUND: Postactivation potentiation (PAP) enhances contractility of skeletal muscle whereas fatigue deteriorates it. Available evidence suggests that the two phenomena may express differently in endurance and power athletes.